SIGNIFICANT INFLUENCES OF VIOLIN EXTRACURRICULAR ACHIEVEMENT TO EMOTIONAL INTELLIGENCE - Salafiyah, Nafik (Harmonia: Journal of Arts Research and Education, 2014)
This research aims to find out (1) whether there is an influence between student’s achievements of learning violin toward their emotional intelligence, (2) whether there is a correlation between student’s achievement of learning violin and their emotional intelligence, and (3) how much contribution of student’s achievement of learning violin to their emotional intelligence. It is a qualitative research which is defined as a research method based on positivism philosophy which is used to study particular sample and population. The sample and population are drawn randomly using research instruments to collect data, and the data are analyzed statistically. This aims to examine the hypothesis defined. The finding shows that there is a significant influence between student’s achievement of learning violin and their emotional intelligence about 76.1%, while the rest of it 23.9% is influenced by other factors which are not studied in this research. It proves that learning violin influences student’s emotional intelligence very much and emotional intelligence is influential in increasing student’s achievement. From the data, it shows that most of the students participating in violin extracurricular are able to increase their learning achievement.